2020
DOI: 10.1136/gpsych-2019-100113
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary life history approach to understanding mental health

Abstract: In recent years, evolutionary life history theory has been used as a heuristic framework to understand mental health. This article reviews the life history theory and its integration with mental disorders and then introduces representative research methods and related empirical studies in the field of evolutionary psychopathology. In the end, this article concludes with future directions for further research examining and developing the evolutionary psychopathological framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 101 publications
1
6
0
1
Order By: Relevance
“…Accordingly, individuals that are physically compromised are less able to cope with undetected threats if they should arise, and should behave more cautiously towards ambiguous stimuli [38]. Similarly, individuals with short lifespans are expected to follow a fast life-history strategy, which has been associated with depression syndromes in humans [39,40]. Together, this evidence supports our initial hypothesis, that tert mutants with shorter telomeres have constitutive pessimistic bias, which may be interpreted in the scope of adaptive life-history theory.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, individuals that are physically compromised are less able to cope with undetected threats if they should arise, and should behave more cautiously towards ambiguous stimuli [38]. Similarly, individuals with short lifespans are expected to follow a fast life-history strategy, which has been associated with depression syndromes in humans [39,40]. Together, this evidence supports our initial hypothesis, that tert mutants with shorter telomeres have constitutive pessimistic bias, which may be interpreted in the scope of adaptive life-history theory.…”
Section: Discussionmentioning
confidence: 99%
“…Degree of future discounting increases by the unpredictability of one's childhood environment (Hill, Jenkins, & Farmer, 2008). Similarly, research on life history strategies has shown that harsh and unpredictable conditions prompt individuals to adopt faster life history strategies involving a shorter and less delayed reward allocation preference, higher impulsivity and lower risk avoidance (Han & Chen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It also aims to understand the brain from the perspectives of developmental and evolutionary biology. 29 By studying the development of the human brain, neuropsychiatric diseases in different life stages-autism in children, depression in the middle-aged and dementia in older adults-will be scrutinised with priority due to their high prevalence in the Chinese population. The study of early dBioBank iagnosis with objective criteria and optimised interventions for these psychotic disorders is encouraged, and associated discoveries are required to have cross-validation in multiple cohorts.…”
Section: The Array Of National Brain Projectsmentioning
confidence: 99%
“…Cognition-related research is highlighted, and it aims to decode cognition-related brain circuitry, explore intelligence in young people, identify treatments for cognitive disorders, and develop neuromorphic computing and brain-machine interfaces simultaneously. It also aims to understand the brain from the perspectives of developmental and evolutionary biology 29. By studying the development of the human brain, neuropsychiatric diseases in different life stages—autism in children, depression in the middle-aged and dementia in older adults—will be scrutinised with priority due to their high prevalence in the Chinese population.…”
Section: The Array Of National Brain Projectsmentioning
confidence: 99%